Students’ Perception of Digital Literacy Competence as Learning Sources - Mega, Iful Rahmawati (Majesty Journal, 2020)
This study was carried out to define the students’ perception of digital literacy competencies as learning sources held by the students of English Education Study Program of STKIP Muhammadiyah Bangka Belitung as active users of internet pointed on the internet searching, hypertext navigation, content evaluation, and knowledge assembly by theory of Paul Gilster (1997). This research uses a descriptive qualitative method. Subjects in this research were 9 students determined using a purposive sampling technique, with the subject criteria is the students who are actively using the internet more than 4 hours a day to browse the internet as educational sources. The results of this research indicate that all of the respondents are not literate yet because they do not have all the indicators in digital literacy. But, only one of nine students answered all the indicators on digital literacy, the respondent has stated as well competencies in internet searching, hypertext navigation, content evaluation, and knowledge assembly. So, from the indicators of digital literacy competencies, it can be implied that only one of nine students who have a good perception of digital literacy as learning sources.